Reading habits among the users of Delhi Public Library, New Delhi: a survey - Sohail, Md.; Alvi, Andleeb (Faculdade de Filosofia e Ciências, 2012)
Study of data collected from 56 users by the administrating questionnaires among their attitudes towards reading habits and purpose of the visiting of libraries at Delhi Public Library, New Delhi, indicate that the, purpose of reading, preference of language, form of library collection, assistance from the library staff in the use of resources and services is necessary to help users meet their information requirements. Finds that people are unable to visit the library regularly due to lack or shortage of time and literature being mostly read by the users are magazines and newspapers.